Benchmarking Adenoma Detection Rates for Colonoscopy: Results From a US-Based Registry. (23rd September 2021) - Shaukat, Aasma; Holub, Jennifer; Pike, Irving M.; Pochapin, Mark; Greenwald, David; Schmitt, Colleen; Eisen, Glenn
Abstract : INTRODUCTION: Adenoma detection rate (ADR) is highly variable across practices, and national or population-based estimates are not available. Our aim was to study the ADR, variability of rates over time, and factors associated with detection rates of ADR in a national sample of patients undergoing colonoscopy. METHODS: We used colonoscopies submitted to the GI Quality Improvement Consortium, Ltd. registry from 2014 to 2018 on adults aged 50–89 years. We used hierarchical logistic models to study factors associated with ADR. RESULTS: A total of 2, 646, 833 colonoscopies were performed by 1, 169 endoscopists during the study period. The average ADR for screening colonoscopies per endoscopist was 36.80% (SD 10.21), 44.08 (SD 10.98) in men and 31.20 (SD 9.65) in women. Adjusted to the US population, the ADR was 39.08%. There was a significant increase in ADR from screening colonoscopies over the study period from 33.93% in 2014 to 38.12% in 2018. DISCUSSION: The average ADR from a large national US sample standardized to the US population is 39.05% and has increased over time.